Qualifizierung laser-additiv gefertigter Komponenten für den Einsatz im Werkzeugbau der Massivumformung - Junker, Daniel (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2021)
Shortened product life cycles and a raised degree of customization require an increased use of flexible manufacturing processes for production. Due to this, additive manufacturing technology is constantly gaining significance within production. Therefore, in this thesis the possibility of using laser-based additive manufacturing processes in toolmaking for bulk metal forming is investigated. The focus is on the resulting material properties, as these are significant for use in toolmaking. In particular, the behavior under tensile and compressive loads as well as the hardness are analyzed. The corresponding structure is identified by using microscopy. The analyzed structures are manufactured by Laser Beam Melting in powder bed and Laser Metal Deposition welding. Furthermore, the influence of a post-heat-treatment is part of the investigations. Based on the results, the potential of additive manufacturing for toolmaking for bulk metal forming is derived and the use of an additively manufactured tool is proven for a selected production sequence through use in serial productio